(untitled) (Journal of Foreign Language Studies, 2019)
With worldwide changes, technological advances and globalization exerting effects on different fields of human activity, in 2016, the Republic of Kazakhstan adopted reforms in general education, including curriculum renewal. As a result, textbooks with revised contents for schools were published. This article describes the “Russian language” textbook developed within the framework of renovating educational program for Grade 10 and 11. The authors, including Prof. Brulyova F.G., Doctor of Education; Associate Professor Kazabeeva V.A, Doctor of Literature and Kornilova T.B., Lecturer have compiled the Russian Language Teaching Materials and Methodology for Grade 10 specializing in humanities. The article discusses the structure of the textbook, justifies the principles to develop the textbook and provides methods to present teaching contents. It also explains the structures of sections, the topic-based distribution of grammatical knowledge and the features of the textbook aimed at fostering critical thinking through reading and writing. The article also describes the "Methodological guide" to the textbook and the collection of dictation and narration exercises included in the Russian Language Teaching Materials and Methodology.